A Comparative Assessment of the Diagnosis of Swallowing Impairment and Gastroesophageal Reflux in Canines and Humans - Ullal, Tarini V.; Marks, Stanley L.; Belafsky, Peter C.; Conklin, Jeffrey L.; Pandolfino, John E. (Frontiers in Veterinary Science, 2022)
Swallowing impairment is a highly prevalent and clinically significant problem affecting people and dogs. There are myriad causes of swallowing impairment of which gastroesophageal reflux is the most common in both species. Similarities in anatomy and physiology between humans and canines results in analogous swallowing disorders including cricopharyngeus muscle achalasia, esophageal achalasia, hiatal herniation, and gastroesophageal reflux with secondary esophagitis and esophageal dysmotility. Accordingly, the diagnostic approach to human and canine patients with swallowing impairment is similar. Diagnostic procedures such as swallowing fluoroscopy, high-resolution manometry, pH/impedance monitoring, and endolumenal functional luminal imaging probe can be performed in both species; however, nasofacial conformation, increased esophageal length, and the difficulty of completing several of these procedures in awake dogs are inherent challenges that need to be considered. Human patients can convey their symptoms and respond to verbal cues, whereas veterinarians must rely on clinical histories narrated by pet owners followed by comprehensive physical examination and observation of the animal eating different food consistencies and drinking water. Dogs may also be unwilling to drink or eat in the hospital setting and may be resistant to physical restraint during diagnostic procedures. Despite the species differences and diagnostic challenges, dogs are a natural animal model for many oropharyngeal and esophageal disorders affecting people, which presents a tremendous opportunity for shared learnings. This manuscript reviews the comparative aspects of esophageal anatomy and physiology between humans and canines, summarizes the diagnostic assessment of swallowing impairment in both species, and discusses future considerations for collaborative medicine and translational research.